EFFECT OF ZINC ADDITION TO DRINKING WATER ON PERFORMANCE AND BEHAVIOR OF GROWING LAMBS DURING HOT CLIMATE - Abbi, Araz Q. S.; Zebari, Hawar M. H.; Barwary, Mwafaq S. Q.; Hidayet, Hoger M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The aim of the current study was to determine whether adding zinc to water will improve lamb performance and behavior during a hot climate. In this experiment, twenty seven lambs were housed indoor in individual pens (1.50 x 1.30m). Zinc was added to the fresh drinking water in three different levels namely T1 (0 mg Zn/day), T2 (36 mg Zn/day) and T3 (72 mg Zn/day). Rumination (m/h), feeding time (m/h), number of visiting feeds (n/h), standing time (m/h), lying time (m/h) and standing bouts (n/h) were recorded three times a day by visual observation. Dry matter intake (kg/d), drinking water intake (litter/day), daily live weight gain and feed conversion ratio were also recorded. The current results indicated that rumination, feeding duration, and the visiting feed number were significantly (P ≤ 0.05) higher in T2 than T1 and T3 groups. However, no-differences were noticed among T1, T2 and T3 groups regarding standing time, lying time, standing bouts, dry matter intake, water intake, daily live weight gain, and feed conversion ratio. In conclusion, adding zinc to fresh drinking water improved rumination, feeding duration and the feed visiting number.